Future global socioeconomic risk to droughts based on estimates of hazard, exposure, and vulnerability in a changing climate - Liu, Yujie; Chen, Jie (The Science of the total environment, 2021)
A consistent and equitable global drought risk assessment for multiple regions, populations, and economic sectors at the gridded scale under future diverse climate change scenarios has been the subject of scarce research. Climate change is projected to increase the future hazard of drought and cause consequential damages to socioeconomic systems. The risk assessment of drought caused by climate change can be a bridge between impacts and adaptation. To assess the socioeconomic risk to droughts in a base period and two future periods (2016 to 2035 and 2046 to 2065), the projections of five general circulation models and population and gross domestic product (GDP), land cover, and water resources data were used to analyze the socioeconomic risk under three scenarios combining representative concentration pathways (RCPs) and shared socioeconomic pathways (SSPs). The socioeconomic risk was calculated as the product of three determinants: hazard, exposure, and vulnerability. The risk of the global population to drought was projected to be highest in 2046 to 2065 under scenario RCP8.5–SSP3, with up to 1.45 × 109 persons affected, a 63% increase compared with the base period. The highest risk to GDP (4.29 × 1013 purchasing power parity $) was possibly in 2046 to 2065 under scenario RCP2.6–SSP1, with the risk increasing 5.64 times compared to the base period. Regions with high socioeconomic risk were primarily concentrated in the East and South Asia, Midwestern Europe, eastern US, and the coastal areas of South America. With climate change, the inequality in future socioeconomic risk to drought among countries is predicted to increase. The ten countries with the highest risks to population and GDP accounted for nearly 70% of the global risk. [Display omitted] •Population risk potentially be highest in RCP8.5–SSP3, with 1.45 × 109 persons affected.•The highest GDP risk is likely in RCP2.6–SSP1 with 5.64 times higher than base period.•Socioeconomic risk distributes unequally and highest in the east and south of Asia.